2022
DOI: 10.1167/tvst.11.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Suspects: The Impact of Risk Factor-Driven Review Periods on Clinical Load, Diagnoses, and Healthcare Costs

Abstract: Purpose To model the healthcare impact (clinical attendance time and financial cost) and clinical outcomes (glaucoma diagnoses) of different risk factor–driven review frequencies for glaucoma suspect patients up until the point of discharge or diagnosis. Methods Medical records of 494 glaucoma suspects were examined to extract the clinical diagnosis. Two criteria for review periods were defined, based on contrasting stringency from established clinical guidelines: Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Such an increased risk might be present in an individual without definitive evidence for either the absence or presence of glaucoma [4][5][6][7] (meaning that a subset may actually have glaucoma that will become definitively diagnosed subsequently) and/or an individual with risk factors for glaucoma development. [8][9][10][11][12][13] The robust characterisation of such risk is foundational to the criteria used to define a POAG suspect, and how they should be managed. However, the NICE guideline for glaucoma 41 concluded that there was insufficient rigorous evidence to recommend a prognostic tool to accurately identify individuals at an increased risk of developing glaucoma, based on a critical review of the quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an increased risk might be present in an individual without definitive evidence for either the absence or presence of glaucoma [4][5][6][7] (meaning that a subset may actually have glaucoma that will become definitively diagnosed subsequently) and/or an individual with risk factors for glaucoma development. [8][9][10][11][12][13] The robust characterisation of such risk is foundational to the criteria used to define a POAG suspect, and how they should be managed. However, the NICE guideline for glaucoma 41 concluded that there was insufficient rigorous evidence to recommend a prognostic tool to accurately identify individuals at an increased risk of developing glaucoma, based on a critical review of the quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, this terminology has also often been used to include individuals with characteristics deemed to be associated with a higher risk of developing glaucoma, such as elevated intraocular pressure. [8][9][10][11][12][13] There are substantially more individuals deemed to be glaucoma suspects than those with definite glaucoma, 14,15 and these individuals form a notable proportion of those under clinical care with a glaucoma-related diagnosis. [16][17][18] High-quality clinical practice guidelines that provide evidence-based guidance on the management of glaucoma suspects might therefore be expected to contribute to minimising the global impact of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focussed on MD as the index of glaucoma progression and beneficial outcome when comparing methods, but this can be further examined using other metrics such as quality-of-life, visual functioning 35 and financial cost, 36,37 which have also been linked to different progression strata. While we have previously shown that the absolute cost in time is minimal at the level of the individual patient, over time and for many patients, this cost is expected to accumulate.…”
Section: Time and MD 'Saved'mentioning
confidence: 99%
“…Deep learning (DL) is a subset of artificial intelligence (AI) based on neural networks that use an active learning strategy in the automated detection of glaucoma based on fundus images [ 36 , 37 ]. It can recognize patterns with glaucomatous features in images quickly and accurately [ 8 ], achieving a robust performance in detecting other retinal pathologies such as diabetic retinopathy and retinopathy of prematurity, macular edema, and age-related macular degeneration [ 32 ], with the potential to assist specialists in mass screening of glaucoma [ 38 ], reducing costs, and offering the potential to solve complex problems involving large datasets with medical images and classify diseases with a good innovative perspective for the introduction of individualized medicine and the optimization of diagnosis and therapy, screening, and prognosis [ 22 , 39 , 40 ], with less dependence on the examiner’s experience [ 5 , 41 , 42 ], demonstrating the potential for implementation of large-scale screening protocols in the population, to screen for glaucomatous papilla in several evolutionary stages and monitor treatments [ 43 ].…”
Section: Computer Vision and Artificial Intelligencementioning
confidence: 99%